2022
DOI: 10.3390/medicina58040523
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neuropathy in Patients Recovering from Severe COVID-19: A Case Series

Abstract: Background and Objectives: Neurological manifestations have been reported in a significant proportion of coronavirus disease 2019 (COVID-19) patients. We aimed to evaluate the prevalence and severity of peripheral nervous system (PNS) involvement in a large group of convalescent COVID-19 patients undergoing in-hospital multidisciplinary rehabilitation. Materials and Methods: Convalescent COVID-19 patients admitted to a Pulmonary Rehabilitation Unit were consecutively screened for inclusion within 48 h of disch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…These findings suggest that peripheral nervous system damage may be a common feature of MIS-C. Interestingly, both central and peripheral nervous system involvement in MIS-C have been previously described 49,50 , although these clinical manifestations are infrequent. Notably, peripheral nervous system damage has also been documented in pediatric and adult COVID-19 and in post-acute sequelae such as long COVID [51][52][53] . Future studies are needed to elucidate the mechanisms and clinical spectrum of neurologic involvement in acute MIS-C and their association with long-term neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that peripheral nervous system damage may be a common feature of MIS-C. Interestingly, both central and peripheral nervous system involvement in MIS-C have been previously described 49,50 , although these clinical manifestations are infrequent. Notably, peripheral nervous system damage has also been documented in pediatric and adult COVID-19 and in post-acute sequelae such as long COVID [51][52][53] . Future studies are needed to elucidate the mechanisms and clinical spectrum of neurologic involvement in acute MIS-C and their association with long-term neurodevelopment.…”
Section: Discussionmentioning
confidence: 99%
“…In patients requiring intensive care, focal neurological deficits have been related to super-imposed mono-neuropathies of unknown etiology [ 36 ]; while in patients with diabetes, severe COVID-19 has been related to neuropathy symptoms and widespread sensory dysfunction [ 37 ]. In Italy, assessment of 102 convalescent patients who were admitted to a rehabilitation clinic showed electrophysiological abnormalities in 42.2% of patients, including peroneal mono-neuropathy in 8.8%, and multiple mono-neuropathy in 8.8% [ 38 ]. In this study, the majority of patients had moderate disease, and showed frequent peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Both these mechanisms may apply in patients with deconditioning (23,24). Furthermore, reduced peripheral oxygen extraction has been shown in COVID-19 patients with small fibre neuropathy, complicating evaluation of exercise limitation even more (25,26).…”
Section: Exercise Capacity and Limitationsmentioning
confidence: 99%